Transition-Metal-Catalyzed Remote C–H Bond Functionalization of Cyclic Amines - Chen, Weijie; Yang, Xiaoyu; Cao, Xi (SynOpen, 2022)
C–H bond functionalization is one of the most effective strategies for the rapid synthesis of cyclic amines containing substituents on the ring, which are core structures of many bioactive molecules. However, it is much more challenging to perform this strategy on remote C–H bonds compared to the α-C–H bonds of cyclic amines. This graphical review aims to provide a concise overview on transition-metal-catalyzed methods for the remote C–H bond functionalization of cyclic amines. Examples are categorized and demonstrated according to mechanistic pathways that initiate the reactions of cyclic amine substrates. Where relevant, selected substrate scope and detailed reaction mechanisms are given.
Keywords: C–H bond functionalization; remote; cyclic amines; transition metals; catalysis; synthesis